2020
DOI: 10.1186/s12866-019-1691-4
|View full text |Cite
|
Sign up to set email alerts
|

HpaXpm, a novel harpin of Xanthomonas phaseoli pv. manihotis, acts as an elicitor with high thermal stability, reduces disease, and promotes plant growth

Abstract: Background: Harpins are proteins secreted by the type III secretion system of Gram-negative bacteria during pathogen-plant interactions that can act as elicitors, stimulating defense and plant growth in many types of nonhost plants. Harpin-treated plants have higher resistance, quality and yields and, therefore, harpin proteins may potentially have many valuable agricultural applications. Harpins are characterized by high thermal stability at 100°C. However, it is unknown whether harpins are still active at te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…In our study, RT-126, -033, -078 and -010 turned out to be the most common ribotypes, each isolated from more than one farm. This finding is in accordance with what we have reported in calves in Italy [ 17 ] and is consistent with the literature, which indicates that these ribotypes as the most common ones in neonatal calves and piglets in Europe and Asia [ 15 , 24 , 34 , 40 , 41 , 54 , 55 , 56 , 57 , 58 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In our study, RT-126, -033, -078 and -010 turned out to be the most common ribotypes, each isolated from more than one farm. This finding is in accordance with what we have reported in calves in Italy [ 17 ] and is consistent with the literature, which indicates that these ribotypes as the most common ones in neonatal calves and piglets in Europe and Asia [ 15 , 24 , 34 , 40 , 41 , 54 , 55 , 56 , 57 , 58 ].…”
Section: Discussionsupporting
confidence: 94%
“…It is known that calves and piglets are among the predominant animals harboring C. difficile . Newborns in general are characterised by higher prevalence rates since age is a key factor that affects the isolation of C. difficile in animals [ 15 ]. The consumption of contaminated meat, due to the high prevalence of C. difficile in livestock animals (including calves and piglets), represents a potential mechanism for transmission [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The wax moth G. mellonella is another model organism used to identify the efficiency and toxicity of antimicrobial agents and is likewise a preferred model organism for avoiding ethical concerns related to the use of mammals. Huang et al [ 61 ] reported that G. mellonella is a leading infection model organism, especially in the field of PDT against Candida albicans and S. aureus. G. mellonella studies investigate light penetration, and Figueiredo-Godoi et al [ 62 ] found that light is distributed 0.27–2.45 mm below cuticle G. mellonella larvae.…”
Section: Preclinical and Clinical Apdt Studiesmentioning
confidence: 99%
“…oryzae to alter the formation of CC and found that N-terminal CC region is essential for eliciting HR, but C-terminus is not. In many studies, the ability of harpin proteins to induce HR was determined by the ratio between the size of the necrotic lesion caused by the HR and the injection site [2,34]. Therefore, we mutated the Hpa1 aa residue at the a, b, or d positions to increase or decrease the PFC, and compared the HR activity of wild Hpa1 and Hpa1 mutants after different temperature treatments to determine their heat resistance.…”
Section: Discussionmentioning
confidence: 99%
“…oryzae (Xoo) [33]; the cassava blight bacteria, X. phaseoli pv. manihotis (Xpm) [34]; and, the bacterial black spot of mango bacteria, X. citri pv. mangiferaeindicae (Xcm) [2].…”
Section: Introductionmentioning
confidence: 99%